Phase and structural changes of nickel catalysts as a function of reaction conditions - De Oliveira, Dominic (Department of Chemical Engineering, 2020)
Carbon dioxide hydrogenation is a route for the production of methane from hydrogen and carbon dioxide, which has attracted increased attention in recent times. It provides a means for both energy storage through substitute natural gas (SNG) production and as a process for the conversion of carbon dioxide into valuable products. Ni is the most widely used metal for SNG production due to its high activity, high selectivity towards methane and low cost in comparison to the other active metals. Ni catalysts have been extensively studied due to their uses in steam reforming and CO methanation, and it is known that deactivation by sintering, sulphur poisoning and carbon formation are the most common deactivation mechanisms for Ni catalysts. Some deactivation of Ni by oxidation has been reported, despite the fact the oxidation of Ni to NiO is not thermodynamically feasible at reaction conditions relevant to Ni catalysts. This has also been observed with Co catalysts for Fischer-Tropsch synthesis applications, where it has been explained that the size dependent oxidation, by produced water, can occur due to the higher surface energy contributions of smaller crystallites. The aim of this project is to study the phase changes of nickel catalysts, specifically through the oxidation of Ni in the presence of steam using in situ magnetic techniques to identify the loss of metallic Ni. As this oxidation is thought to be a size dependent effect, a set of catalysts with narrow crystallite size distributions and tuneable size is required for the experimental testing. The use of organometallic precursor reduction (OPR) and homogeneous deposition precipitation (HDP) was investigated for the synthesis in this study. OPR produced unsupported nanoparticles with a suitable size, however the occurrence of sintering during the anchoring and supporting of these nanoparticles on silica spheres, due to the high temperature calcination step, made these catalysts unsuitable for use in the oxidation study. The catalysts synthesised by HDP produced supported nickel catalysts with high loadings and sizes of 3.6 and 7.5 nm, with minimal overlap of size distributions, making them suitable for oxidation testing. The size of these nanoparticles was controlled by varying the reduction temperature. The HDP catalysts were tested at model conditions (i.e. in the absence of CO2) where the partial pressure ratios of steam to hydrogen, simulating different conversion levels, were increased up to a steam to hydrogen ratio of 400, to determine at what ratio the catalysts would begin to oxidise. The smaller catalysts showed significant oxidation at lower partial pressure ratios and to a greater extent than the larger particle size. These results showed the size dependence of the oxidation, with the large particles showing greater resistance to oxidation. These results were compared to iii thermodynamic calculations made for the size dependent oxidation of Ni, and good agreement between the experimental and predicted results was observed. The use of magnetic characterisation of the particle size was conducted by application of the Langevin equation as well as by a dispersion measurement, carried out by the titration of the Ni surface with H2. These in situ characterisation techniques showed consistency with the conventional external characterisation techniques and also showed that no size changes occurred throughout the testing, indicating that the results are truly due to size effects. Upon re-reduction of the oxidised catalysts, the full recovery of oxidised Ni was achieved with the large sample, whereas the smaller sample only achieved 60 % recovery of oxidised material. This is thought to be due to the formation of a less reducible phase, specifically metal-support compounds such as nickel silicate.